1990
DOI: 10.1007/bf01437178
|View full text |Cite
|
Sign up to set email alerts
|

The structure of C2H4 clusters from theoretical interaction potentials and vibrational predissociation data

Abstract: Optimized geometries and binding energies are calculated for ethene (ethylene) dimers, trimers, and tetramers based on a pairwise additive dimer potential. From these results intermolecular frequencies and relative abundancies (catchment areas) of the different isomers are obtained and compared with the results of accurate measurements of the photodissociation upon absorption of one photon of a CO 2 laser in the region of the v7 monomer absorption band at 949 cm-~. The clusters are size selected in a scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
6
18
0
Order By: Relevance
“…Alberts et al [9] carried out ab initio calculations at the MP2 level, in which the D 2d cross form was not taken into account. Tsuzuki and Tanabe [11] calculated energies of a variety of dimer structures at the MP2/6-311G(2d, 2p) level and concluded that the D 2d structure is the most stable, in agreement with the results obtained by Ritter and Gruen [6], Chan et al [5], and Ahlrichs et al [7].…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Alberts et al [9] carried out ab initio calculations at the MP2 level, in which the D 2d cross form was not taken into account. Tsuzuki and Tanabe [11] calculated energies of a variety of dimer structures at the MP2/6-311G(2d, 2p) level and concluded that the D 2d structure is the most stable, in agreement with the results obtained by Ritter and Gruen [6], Chan et al [5], and Ahlrichs et al [7].…”
Section: Introductionsupporting
confidence: 71%
“…In the study by Ahlrichs et al [7], the intermolecular potential is constructed with the aid of ab initio calculations with no electron correlation effect. Tsuzuki and Tanabe [11] indicate that potentials of the ethylene dimer without the electron correlation effect are very shallow.…”
Section: Calculationmentioning
confidence: 99%
See 3 more Smart Citations